PENGARUH HUMAN RELATION TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. JALUR NUGRAHA EKAKURIR PEKANBARU - Afrian Rahman; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Human resources in each company is the driving factor of the overall activities undertaken, it shows that in the absence of manpower then the company's activities or activities of the company will not be able to run even though the company has many other resources. To have skilled employees, have the ability to work and loyal to the company, is not an easy thing. Many of the determining factors are human relation.This research was conducted at PT. Jalur Nugraha Ekakurir (JNE) which is located at Jalan Sisingamaharaja No. 65 Pekanbaru. The purpose of this study was conducted to determine and analyze the influence of human relations to employee job satisfaction At PT. JNE Pekanbaru.In this research the methodology used is descriptive and quantitative with SPSS program, where the sample used is employees of PT. JNE Pekanbaru and as a source of information is the HRD, Front Office and Marketing Manager. To determine the sample using the census method or the total of the total population of employees working at PT. JNE Pekanbaru consisting of 43 people. Data collection techniques through interviews, observations and questionnaires.From the result of data analysis which consist of validity, reliability, and simple linear regression, human relation in this research cover 5 dimension, that is adany akomunikasi, the direction, the openness, the existence of mutual respect and the existence of loyalty. Each has a related indicator and have a positive effect on employee job satisfaction at PT. JNE Pekanbaru.Keywords: Human Relation, Job Satisfaction